2021
DOI: 10.21037/tau-21-575
|View full text |Cite
|
Sign up to set email alerts
|

A ureteral stricture disease score and classification system: correlation with upper urinary tract reconstructive surgery complexity

Abstract: Background: To develop an original and standardized ureteral stricture disease (USD) score and classification system for quantifying ureter stricture characteristics, assessing complexity of the minimally invasive upper urinary tract reconstructive (UUTR) surgical procedure, formulating preoperative plans, and offering objective comparisons of surgical techniques between different institutions and surgeons.Methods: We retrospectively reviewed a test set of 64 patients and a validation set of 170 patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Below are factors reported that may affect treatment outcomes of benign ureteral strictures: length and location of stricture, stricture duration, and renal function. 20,21 Therefore, the multivariate analysis was used to assess the influencing factors simultaneously. However, our results showed that only the surgical method was the independent risk factor affecting success rate and recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Below are factors reported that may affect treatment outcomes of benign ureteral strictures: length and location of stricture, stricture duration, and renal function. 20,21 Therefore, the multivariate analysis was used to assess the influencing factors simultaneously. However, our results showed that only the surgical method was the independent risk factor affecting success rate and recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Below are factors reported that may affect treatment outcomes of benign ureteral strictures: length and location of stricture, stricture duration, and renal function 20,21 . Therefore, the multivariate analysis was used to assess the influencing factors simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Villanueva ( 17 ) suggested that it was unnecessary to open the bladder in the UU method, which thus had a smaller trauma than the UC method. The UC method is prone to bladder spasm or leakage, which may impair the bladder function, especially in children younger than 1 year, and may induce ureteral opening stenosis or vesicoureteral reflux ( 18 ). In our center, there was no case of vesicoureteral reflux or ureteral opening stenosis with the UC method.…”
Section: Discussionmentioning
confidence: 99%